Contrast-enhanced ultrasound combined targeted microbubbles for diagnosis of highly aggressive papillary thyroid carcinoma - Ma, Jiaojiao; Wang, Yuan; Xi, Xuehua; Tang, Jiajia; Wang, Linping; Wang, Liangkai; Wang, Di; Liang, Xiaolong; Zhang, Bo (Frontiers in Endocrinology, 2023)
Background: Overdiagnosis and overtreatment of thyroid cancer (TC) has become a worldwide problem. Accurate diagnosis of highly aggressive TC may greatly help avoid overtreatment. However, a convenient and accurate method is still lacking. Targeted microbubbles, an emerging ultrasound contrast agent, have the potential to accurate diagnosis of highly aggressive thyroid cancer. Purpose: The purpose of this research is to design and prepare a targeted microbubbles for specific contrast-enhanced ultrasound (CEUS) imaging of highly invasive TC. Methods: Using β-galactoside-binding protein galectin-3 (Gal-3) overexpressed on the surface of highly invasive TC cells as a target, C12 polypeptide (ANTPCGPYTHDCPVKR) with high affinity and specificity for Gal-3 was coupled to the surface of lipid microbubbles to prepare targeted microbubbles (Gal-3-C12@lipo MBs). The targeted microbubbles were prepared by thin-film hydration method and mechanical shaking method. The morphology, diameter, concentration and stability of microbubbles were investigated by fluorescence microscopy and an AccuSizer. The biosafety of microbubbles was studied using BCPAP cells through CCK8 assay. Confocal laser scanning microscope and flow cytometry were applied to research the cellular uptake of microbubbles to investigate the targeting ability to highly aggressive TC. Finally, the specific contrast-enhanced ultrasound imaging of microbubbles in highly invasive TC was validated on the BCPAP mouse subcutaneous tumor model via a clinically ultrasound imaging system. Results: Gal-3-C12@lipo MBs were successfully prepared which showed a well-defined spherical morphology with an average diameter of 1.598 ± 0.848 μm. Gal-3-C12@lipo-MBs showed good stability without rupture within 4 hours. At the cellular level, Gal-3-C12@lipo MBs exhibited favorable biosafety and superior targeting ability to BCPAP cells, with 2.8-fold higher cellular uptake than non-targeting lipid microbubbles (Lipo MBs). At the animal level, Gal-3-C12@lipo MBs significantly improved the contrast-enhanced ultrasound imaging in highly invasive TC, with a tumor intensity significantly higher than that of non-targeted Lipo MBs. Conclusion: We designed and fabricated a novel targeted microbubbles for the specific ultrasound imaging diagnosis of highly aggressive TC. The targeted microbubbles have good stability, superior biosafety and high targeting specificity, which can significantly improve the tumor signal-to-noise ratio of highly invasive TC, and have the potential to facilitate and accurately diagnose highly invasive TC.